El régimen legal de las sociedades por acciones simplificadas (sas) en Ecuador: desafíos jurídicos y regulatorios en su implementación y funcionamiento. - Reyes Carrera Génesis Gabriela (2025)
This research work is developed within the scope of corporate law, analyzing one of the newest legal entities introduced in the Companies Law and operating in the country since 2020: Simplified Stock Companies (SAS). These are a type of commercial company framed within modern law, for which bureaucratic procedures have been simplified, introducing new parameters for their incorporation requirements compared to other types of companies that have traditionally operated in the country. In response to the pandemic, new societal needs emerged, one of which was the proliferation of entrepreneurship. To formalize these ventures, Ecuador introduced the Simplified Stock Companies under the Entrepreneurship and Innovation Law enacted in 2020. This type of commercial company can be constituted by one or more natural or legal persons through a simplified process, most importantly, at no cost. The key advantage of this type of company lies in the ease it offers entrepreneurs to legally regularize their businesses through a framework that requires fewer bureaucratic procedures and whose flexibility significantly fosters entrepreneurship. Simplified Stock Companies were incorporated into the Companies Law in 2020 through reform provisions published in the Official Register Supplement 151 of February 28, 2020. These provisions essentially regulate their implementation and operation. This is where the essence of this research lies, as it becomes necessary to analyze the legal provisions that support this type of commercial company to identify potential challenges and demonstrate how this corporate legal structure has contributed to the country's economic development. 6 This analysis also considers evaluating the operational capacity of these companies in the commercial sphere and the mechanisms for supervising their functioning when all procedures are carried out virtually. It is essential to determine the means for ensuring data protection and verification, as well as the authenticity and legality of digitally submitted documents. This study aims to identify whether the existing regulations are sufficient to govern the functioning of Simplified Stock Companies under the conditions established. To conduct this analysis, a descriptive and explanatory research approach is employed. This approach not only describes the fundamental characteristics of the SAS legal framework but also explains the challenges and obstacles faced by both entrepreneurs and regulatory authorities in its practical application. Quantitative, qualitative, and analytical methods are used to achieve a comprehensive understanding of the topic. The analysis is complemented by an analytical approach that seeks to identify the root causes of the challenges. This is achieved through a study of the relevant regulations. Additionally, the legal implications of SAS are explored, focusing on their legal implementation within Ecuadorian corporate law, including shareholder liability, management flexibility, and financing opportunities. Keywords: Simplified Stock Companies, regulatory framework, efficiency, corporate regime.